Downregulation of microRNA‐100/microRNA‐125b is associated with lymph node metastasis in early colorectal cancer with submucosal invasion. Issue 3 (March 2017) - Fujino, Yasuteru; Takeishi, Shunsaku; Nishida, Kensei; Okamoto, Koichi; Muguruma, Naoki; Kimura, Tetsuo; Kitamura, Shinji; Miyamoto, Hiroshi; Fujimoto, Akiko; Higashijima, Jun; Shimada, Mitsuo; Rokutan, Kazuhito; et al.
Abstract : A majority of early colorectal cancers (CRCs) with submucosal invasion undergo surgical operation, despite a very low incidence of lymph node metastasis. Our study aimed to identify microRNAs (miRNAs) specifically responsible for lymph node metastasis in submucosal CRCs. MicroRNA microarray analysis revealed that miR‐100 and miR‐125b expression levels were significantly lower in CRC tissues with lymph node metastases than in those without metastases. These results were validated by quantitative real‐time PCR in a larger set of clinical samples. The transfection of a miR‐100 or miR‐125b inhibitor into colon cancer HCT116 cells significantly increased cell invasion, migration, and MMP activity. Conversely, overexpression of miR‐100 or miR‐125b mimics significantly attenuated all these activities but did not affect cell growth. To identify target mRNAs, we undertook a gene expression array analysis of miR‐100‐silenced HCT116 cells as well as negative control cells. The Ingenuity Pathway Analysis, TargetScan software analyses, and subsequent verification of mRNA expression by real‐time PCR identified mammalian target of rapamycin (mTOR) and insulin‐like growth factor 1 receptor (IGF1R) as direct, and Fas and X‐linked inhibitor‐of‐apoptosis protein (XIAP) as indirect candidate targets for miR‐100 involved in lymph node metastasis. Knockdown of each gene by siRNA significantly reduced the invasiveness of HCT116 cells. These data clearly show that downregulation of miR‐100 and miR‐125b is closely associated with lymph node metastasis in submucosal CRC through enhancement of invasion, motility, and MMP activity. In particular, miR‐100 may promote metastasis by upregulating mTOR, IGF1R, Fas, and XIAP as targets. Thus, miR‐100 and miR‐125b may be novel biomarkers for lymph node metastasis of early CRCs with submucosal invasion. Abstract : Downregulation of miR‐100 and miR‐125b is closely associated with lymph node metastasis in early colorectal cancer (CRC) with intrasubmucosal invasion through enhancement of invasion, motility, and matrix metalloproteinase activity. In particular, miR‐100 may promote lymph node metastasis by upregulating mTOR and IGF1R as direct targets, and Fas and XIAP as indirect targets. Our data clearly indicate that miR‐100 and miR‐125b may be novel biomarkers for lymph node metastasis of early CRCs with submucosal invasion.